The making of a community: The making of a photo collection in a rural community in Italy - Michele F. Fontefrancesco (University of Belgrade, 2016)
Photos are by their very nature evocative objects (Turkle 2007). This paper investigates the ability of a photo's capacity to trigger narratives about the self and the past. It argues that the collection of historic, private photos and the creation of a public photographic archive build a sense of community.